2019
DOI: 10.1016/j.trci.2019.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's disease mechanisms in peripheral cells: Promises and challenges

Abstract: Introduction Development of efficacious therapeutic interventions for Alzheimer's disease (AD) is hampered by the lack of understanding early disease mechanisms, biomarkers, and models that mimic complex pathophysiology of human disease. Methods This article aims to assess to what extent peripheral cells recapitulate molecular mechanisms altered in the brain and could be used as translational models for the development of individualized medicine for AD. Results Multiple studies suggest that AD is a systemic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 91 publications
0
24
0
Order By: Relevance
“…In our study, we used primary dermal fibroblasts from sAD patients. It was demonstrated that AD-related pathological changes are not limited to neurons, but can also be observed in peripheral cells, including fibroblasts [23,37]. In contrast to postmortem brain specimens, fibroblast cultures allow us to investigate the earlier stages of disease development and to analyze vital cellular processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we used primary dermal fibroblasts from sAD patients. It was demonstrated that AD-related pathological changes are not limited to neurons, but can also be observed in peripheral cells, including fibroblasts [23,37]. In contrast to postmortem brain specimens, fibroblast cultures allow us to investigate the earlier stages of disease development and to analyze vital cellular processes.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of reports have shown that mitochondrial dysfunction is an early event in AD development [10,18,19] and that this dysfunction is not limited to neurons, but may also be observed in the peripheral tissues of AD patients [20][21][22][23][24]. Alterations in mitochondrial homeostasis affect multiple aspects of cellular function, including calcium handling, redox homeostasis and metabolism.…”
Section: Fibroblasts From Sad Patients Show Signs Of Increased Cellul...mentioning
confidence: 99%
“…This limitation potentially leads to wrong conclusions about the pathogenic mechanisms and ultimately may dampen the development of effective therapies. Alternatively, patient-derived cells of neuronal lineage such as those from the olfactory epithelium may provide a convenient solution to this problem [5,9,42]. On the other hand, the accumulation of superoxide anion increases the levels of compounds such as 4-hydroxynonenal (4-HNE).…”
Section: Alzheimer's Disease-related Oxidative Stress In the Olfactory Epithelium And Onpsmentioning
confidence: 99%
“…Although the manifestations of AD are preponderantly cerebral, cumulative evidence shows that AD is a systemic disorder [5]. Accordingly, molecular changes associated with AD are not exclusively manifested in the brain but include cells from different parts of the body, ranging from the blood and skin to peripheral olfactory cells.…”
Section: Introductionmentioning
confidence: 99%
“…Aβ deposition interacts with glial cells, pericytes, and neurons, modifies BBB and leads to immune cell infiltration ( 49 ). Those infiltrated cells and inflammatory mediators induce a proinflammatory environment around the lesion, which eventually leads to neuroinflammation and neurodegeneration ( 50 , 51 ). Current study concluded that the systematic immune response also involves in the neuroinflammation for which there is a large amount of evidence suggesting a proinflammatory state in AD patient, which implicates the complicated influence of immunosenescence in this disease ( 50 ).…”
Section: Immunosenescence Is a Promising Amplifier For Neuro-inflammamentioning
confidence: 99%